Rough weather - Parker, Robert B., 1932- (New York : G.P. Putnam's Sons, 2008)
Parker once again proves he is a force of nature in this mystery where a hurricane hinders a kidnapping and Spenser goes on a search for the man responsible--the infamous Gray Man, who has both helped and hunted Spenser in the past.
Map on endpapers.
Keywords: Spenser (Fictitious character) -- Fiction; Private investigators -- Massachusetts -- Boston -- Fiction; Kidnapping -- Fiction; Hurricanes -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction